The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5935/0101-2800.2014s005
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation in anemia treatment

Abstract: Pacientes com DRC estágios 1 e 2 deverão receber suplementação de ferro para manter os níveis de ferritina sérica e saturação de transferrina dentro dos valores da população geral (Opinião). recomendAção 3.2Pacientes com DRC estágios 3,4 e 5ND deverão receber suplementação de ferro para manter os níveis de ferritina sérica maior que 100 ng/mL e saturação de transferrina maior que 20% (Opinião); recomendAção 3.3Pacientes com DRC em estágio 5 dialítico deverão receber suplementação de ferro para manter os níveis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
2
0
3
Order By: Relevance
“…The global management of hemodialysis patients includes iron reserve monitoring as an essential component, because iron deficiency is closely associated with an inadequate response to ESA treatment ( 6 , 38 , 39 ). Our results reflected this relationship and demonstrated that increased serum iron was associated with diminished treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The global management of hemodialysis patients includes iron reserve monitoring as an essential component, because iron deficiency is closely associated with an inadequate response to ESA treatment ( 6 , 38 , 39 ). Our results reflected this relationship and demonstrated that increased serum iron was associated with diminished treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Com os valores laboratoriais, adotou-se as seguintes referências de normalidade: <150 mg/dL para triglicerídeos; <190 mg/dL para colesterol total; <150 mg/dL para o LDL-c; <160 mg/dL para o não HDL-c 9 ; <100 mg/dL para glicemia 10 ; >40 mg/dL de HDL-c para mulheres e >50 mg/dL de HDL-c para homens 11 ; de 0,6 a 1,3 mg/dL para creatinina 12 ; de 15-45 mg/dL para ureia.…”
Section: Métodosunclassified
“…Renal biomarkers, such as neutrophil gelatinase-associated lipocalin (NGAL) and retinol-binding protein (RBP), have been used in the early identification of renal injury, especially in acute renal failure [15] and tubular dysfunction [16,17], signaling it even before the perception of the decrease in the glomerular filtration rate (GFR) associated with the increase in serum creatinine. They also appear to be potential biomarkers during therapy with nucles(t)ide analogs [18,19]…”
Section: Introductionmentioning
confidence: 99%